The Inclusion of Third Parties (Joinder) in Multi-Party International Arbitration Cases: The Perspective of Indonesian Arbitration - King William; Gatot P. Soemartono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Indonesia also officially recognizes international arbitration, which is articulated in Article 1 paragraph (9) of the Arbitration Law, as amended following Constitutional Court Decision No. 100/PUU-XXII/2024. This provision states: